2017
DOI: 10.1136/bjsports-2016-097270.162
|View full text |Cite
|
Sign up to set email alerts
|

Concussion incidence and mechanism among youth volleyball players

Abstract: ObjectiveTo assess the incidence of concussions among adolescent volleyball players in Canada.DesignCross sectional survey.SettingOnline survey.ParticipantsIn total, 663 registered Volleyball Canada members completed a national survey, with a response rate of 13.0%; web-based survey response rates rarely exceed 5%. The 452 (68.2%) female and 211 (31.8%) male responders had a mean age of 16.2 (95% CI: 16.1to 16.4) years with a range from 14 to 19 years.Assessment of risk factorsThe type of environment: controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our detected concussion rate of 7.5% in indoor athletes confirmed the results of a previous survey in 663 registered Volleyball Canada members in which the incidence of concussion was estimated as 7.1 per 100 male volleyball players and 7.5 per 100 female volleyball players. 10 In the study by Meeuwisse et al, ball-to-head contact was the most common mechanism of injury, followed by player-to-player contact (20.2%) and player-to-floor contact (15.5%). In addition, Meeuwisse et al 10 reported that almost half of the concussion injuries occurred during practice (46.5%), while the rest occurred during the game (38.4%) or in warm-up (15.1%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our detected concussion rate of 7.5% in indoor athletes confirmed the results of a previous survey in 663 registered Volleyball Canada members in which the incidence of concussion was estimated as 7.1 per 100 male volleyball players and 7.5 per 100 female volleyball players. 10 In the study by Meeuwisse et al, ball-to-head contact was the most common mechanism of injury, followed by player-to-player contact (20.2%) and player-to-floor contact (15.5%). In addition, Meeuwisse et al 10 reported that almost half of the concussion injuries occurred during practice (46.5%), while the rest occurred during the game (38.4%) or in warm-up (15.1%).…”
Section: Discussionmentioning
confidence: 95%
“…10 In the study by Meeuwisse et al, ball-to-head contact was the most common mechanism of injury, followed by player-to-player contact (20.2%) and player-to-floor contact (15.5%). In addition, Meeuwisse et al 10 reported that almost half of the concussion injuries occurred during practice (46.5%), while the rest occurred during the game (38.4%) or in warm-up (15.1%). We did not record the mechanism or setting (game vs practice) of concussion injury in our study.…”
Section: Discussionmentioning
confidence: 95%
“…This prospective cohort study was conducted at the 2018 Volleyball Canada (VC) Youth Nationals tournament (May [16][17][18][19][20][21][22]2018). This study was approved by the University of Calgary Research Ethics Board (REB18-0343).…”
Section: Methodsmentioning
confidence: 99%
“…Particular attention was paid to concussion in Canadian youth volleyball following a cross-sectional survey which determined that 15.1% of all volleyball-related concussions were sustained during the hitting warm-up. 20 In response to this finding, VC introduced a warm-up rule change which prevented athletes from travelling underneath the net following their attack attempt. This rule change was introduced for the 2018 Canadian Youth National Volleyball Championships.…”
Section: Response To Volleyball Canada Rule Changesmentioning
confidence: 99%
“…There has also been an increase in the amount of research, media coverage, educational and policy interventions addressing the phenomenon (Sarmiento et al, 2017 ). In particular, a substantial body of biomedical research on sport-related concussion has been conducted in different sports, such as horse racing (Mattacola et al, 2017 ), ice hockey (Tegner and Lorentzon, 1996 ), rugby (Gardner et al, 2015 ), combat sports (Follmer et al, 2020 ), volleyball (Meeuwisse et al, 2017 ), and football (Leung et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%